Answer:
![(3x^2+7x-20)/(x+4)=3x-5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/qr2bj36o15s6ge7bvvcdi3wsqllg1y0ebk.png)
Explanation:
Long division:
Step 1:
We divide '3x²' by 'x' to get the first term of quotient.
⇒
![(3x^2)/(x)=3x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/76vg1zcpiucxalq5m12sda20wn0atp5pjs.png)
Now, we multiply '3x' to
![(x+4)](https://img.qammunity.org/2020/formulas/mathematics/high-school/4dm82x9hgtjm0x10kqfm6iip73yngjbhng.png)
⇒
![3x(x+4)=3x^2+12x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ghm5mkwkumjpi0nq1e1wbyclk7ufrm580f.png)
Now, we subtract
from the given numerator
. This gives,
![=3x^2+7x-20-(3x^2+12x)\\=3x^2+7x-20-3x^2-12x\\=3x^2-3x^2+7x-12x-20\\=-5x-20](https://img.qammunity.org/2020/formulas/mathematics/middle-school/a7m52lsq0k535zs658a841q3094hlmgm6n.png)
Step 2:
We divide the first term of the above result by 'x' again to get the second term of the quotient.
⇒
![(-5x)/(x)=-5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8sxgchur245mhsxjaqxxs8kazpnhmyxvs4.png)
Now, we multiply '-5' to
![(x+4)](https://img.qammunity.org/2020/formulas/mathematics/high-school/4dm82x9hgtjm0x10kqfm6iip73yngjbhng.png)
⇒
![-5(x+4)=-5x-20](https://img.qammunity.org/2020/formulas/mathematics/middle-school/1c50dctoubf6zl8721tarbwtg03o4ueie7.png)
Now, we subtract
from the result obtained at the last of step 1
. This gives,
![-5x-20-(-5x-20)=-5x+5x-20+20=0](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ggwtfh5atb0bv74ewe4w4owip9q8wth5v1.png)
So, we stop division as we got a constant after subtraction. The constant is called the remainder and here the remainder is 0.
The quotient is our answer:
![3x-5](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ha5g5rh1taee7kp1itjsdeo2nzzj3ka5cy.png)